2016
DOI: 10.1016/j.annemergmed.2016.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Saving Lives and Protecting People From Injuries and Violence

Abstract: Emergency physicians witness the impact of injury and violence every day. Traumatic brain injury, assault-related trauma, motor vehicle crashes, and drug overdoses make up only some of these injuries-many of which can be prevented and better understood. CDC's National Center for Injury Prevention and Control-the Injury Center-is uniquely poised to measure the toll of injury and violence on the lives of Americans, to communicate such injury inequities, and to reduce the factors that increase their risk.Injury i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In addition, a study in South Africa showed a higher survival rate among victims of sharp (stabbing) wounds, compared to gunshot wounds, reflecting the serious wounding capacity of firearms . Gunshot injuries impact on both the criminal justice and the public healthcare systems, and studies like the present one are essential for providing statistics to improve public policies in this area …”
Section: Discussionmentioning
confidence: 92%
“…In addition, a study in South Africa showed a higher survival rate among victims of sharp (stabbing) wounds, compared to gunshot wounds, reflecting the serious wounding capacity of firearms . Gunshot injuries impact on both the criminal justice and the public healthcare systems, and studies like the present one are essential for providing statistics to improve public policies in this area …”
Section: Discussionmentioning
confidence: 92%
“…Violence is a serious public health problem that affects people of both genders, at all stages of life, from children to aged people 1 . In all its forms, it casts a long shadow over the health of populations and individuals and has spurred several organizations over the past few decades to focus efforts to significantly reduce its prevalence 2 .…”
Section: Introductionmentioning
confidence: 99%